UCP2 I/D Modulated Change in BMI During a Lifestyle Modification Intervention Study in Japanese Subjects - Mutombo, P.B. (Mary Ann Liebert, Inc., 2013)
Aim: Polymorphisms in uncoupling protein (UCP) genes have been strongly associated with energy expenditure and obesity. This study aimed at investigating the effects of UCP gene polymorphisms (UCP1 −3826A/G, UCP2A/V, UCP2 I/D, and UCP3 −55C/T) on change in body mass index (BMI) during a lifestyle modification program in Japanese subjects. Results: Intervention induced a significant decrease in energy intake (−8.6%±17.0%) and a significant increase in energy expenditure (7.7%±7.4%). As a result, participants experienced a significant decrease in their BMI of −1.8%±2.7%. In a multivariate regression analysis, only UCP2 D/I among the selected UCP gene polymorphisms was associated with a change in BMI independent of the effects of gender, age, baseline BMI, changes in energy intake, and expenditure. Further regression analysis revealed that, in contrast to the DD genotype group, the DI+II genotype group showed no significant association between weight loss and change in energy expenditure suggesting this polymorphism altered the effects of this parameter on change in BMI. Conclusion: The study found UCP2 D/I to be associated with change in BMI by altering the effect of change in energy expenditure on change in BMI.